Analisis Peran Media Sosial sebagai Salah Satu Kekuatan Kampanye Calon Legislatif PDI Perjuangan di Pemilu 2024 - Mohamad Safii (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to analyze the role of social media as a strategic force in the campaign of legislative candidates from the Indonesian Democratic Party of Struggle (PDI Perjuangan) in the 2024 General Election. Amidst increasing internet penetration and social media usage in Indonesia, especially among the younger generation, social media has become a primary means of political communication. In this context, social media functions not only as a tool for disseminating information, but also as an interactive medium capable of shaping public perception, building political image, and significantly expanding campaign reach. This study uses a qualitative approach through literature review and content analysis of the social media accounts of several PDI Perjuangan legislative candidates, such as Ir. Bambang Wuryanto, Bagus Suryokusumo, and Muhammad Iqbal Adila. The results of the study indicate that strategic use of social media can increase political exposure and emotional closeness with constituents. Authentic, consistent content that emphasizes relevant political values has proven effective in attracting voter attention and building community engagement. Social media also allows legislative candidates to respond to current issues quickly and personally, and mobilize support more efficiently than conventional campaign methods. Thus, the findings of this study confirm that social media plays a very important role in modern political campaign strategies, and is one of the determining factors for success in legislative contests in the digital era.